2019
DOI: 10.1136/bmjresp-2018-000394
|View full text |Cite
|
Sign up to set email alerts
|

First patient-centred set of outcomes for pulmonary sarcoidosis: a multicentre initiative

Abstract: IntroductionRoutine and international comparison of clinical outcomes enabling identification of best practices for patients with pulmonary sarcoidosis is lacking. The aim of this study was to develop a standard set of outcome measures for pulmonary sarcoidosis, using the value-based healthcare principles.MethodsSix expert clinics for interstitial lung diseases in four countries participated in a consensus-driven RAND-modified Delphi study. A mixed-method approach was applied for the identification of an outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Patient-reported outcome measures and the six-minute walk test have been recommended in disease assessment [30]. A recent international Delphi study supported multi-faceted outcomes to assess disease severity for clinical and research purposes, including spirometry/DLCO, quality of life, assessment of progression as well as a biomarker [31]. These data support the importance of defining a comprehensive biomarker of disease progression.…”
Section: Discussionmentioning
confidence: 95%
“…Patient-reported outcome measures and the six-minute walk test have been recommended in disease assessment [30]. A recent international Delphi study supported multi-faceted outcomes to assess disease severity for clinical and research purposes, including spirometry/DLCO, quality of life, assessment of progression as well as a biomarker [31]. These data support the importance of defining a comprehensive biomarker of disease progression.…”
Section: Discussionmentioning
confidence: 95%
“…35 More recently, an outcome measures set was defined for pulmonary sarcoidosis based on a multicenter initiative consisting of seven outcome measures: mortality, pulmonary function, soluble interleukin-2 receptor change as an activity biomarker, weight gain, quality of life, osteoporosis, and clinical outcome status. 36 It is hoped that this will establish a common ground for future studies on both monitoring and treatment of this condition. Similarly, imaging modalities including CT scan with CT activity score and positron emission tomography (PET)/CT are gaining increased attraction as potential tools to measure efficacy of treatment although further studies are needed before recommending either of them.…”
Section: Principles Of Managementmentioning
confidence: 97%
“…A recent multinational initiative, evaluating the feasibility of a set of the best standardized practice outcome measures for patients with sarcoidosis, has proposed that the KSQ and Fatigue Assessment Score (vide infra) be used as the standard PROMs for assessing HRQoL in patients with pulmonary sarcoidosis. 51,52 The Sarcoidosis Assessment Tool…”
Section: Sarcoidosis Health Questionnairementioning
confidence: 99%
“…153 Subsequent studies have, however, shown the FAS to be a robust instrument and a recent multinational initiative has recommended the FAS as the PROM of choice for assessing fatigue in sarcoidosis. 51,52 Studies utilizing the FAS have shown that sarcoidosisassociated fatigue occurs more commonly in females, 152,155 and has been associated with an increased sense of dyspnea, reduced 6MWD, and reduced exercise tolerance. 67 It is more severe in patients with pulmonary and extrapulmonary disease versus those with isolated pulmonary involvement.…”
Section: Fatigue Assessment Scalementioning
confidence: 99%
See 1 more Smart Citation